Molecular cloning and functional characterization of two insect chitin deacetylases from the American white moth, Hyphantriacunea. (22nd March 2021) - Zhao, Dan; Wu, Han; Yan, Xiaoping; Guo, Wei; Lu, Xiujun; Guo, Xiaochang; Liu, Zhaorui; Li, Yazi
Abstract: Chitin deacetylases (CDAs) convert chitin into chitosan and play crucial roles in the insect biological processes, including growth and development. In this study, two CDA‐encoding genes, HcCDA1 and HcCDA4, were identified from Hyphantria cunea . Conserved Domain Database for HcCDA1 identified a chitin‐binding peritrophin‐A domain (ChBD), a low‐density lipoprotein receptor class A domain (LDLa), and a putative CDA‐like catalytic domain (CDA), whereas HcCDA4 lacked the LDLa domain. Phylogenetic comparison with other insect CDAs revealed that HcCDA1 belonged to the insect group I CDA and HcCDA4 belonged to group III. qRT‐PCR results showed that HcCDA1 and HcCDA4 were more highly expressed in newly moulted 5th‐instar larvae, and HcCDA1 was highly expressed in the integument, whereas HcCDA4 was abundantly transcribed in the integument and hindgut. Western blot revealed that the expression of HcCDA1 and HcCDA4 in translational levels were consistent with the transcription. Double‐stranded RNA injection of HcCDA1 and HcCDA4 into H. cunea larvae significantly reduced HcCDA transcript levels, resulted in larval–pupal moulting difficulty, and produced high larval mortality. These results demonstrate important contributions of HcCDA1 and HcCDA4 to insect moulting and development and provide potential new targets for designing effective double‐stranded RNA‐based pesticides to protect crops.